2007
DOI: 10.1007/s00223-007-9000-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone Formation Zones in Heterotopic Ossifications: Histologic Findings and Increased Expression of Bone Morphogenetic Protein 2 and Transforming Growth Factors ß2 and ß3

Abstract: Heterotopic ossifications (HOs) formed after total endoprosthetic replacement of the hip joint were collected during revision surgery (n = 7). Tissues collected during regular hip arthroplasty (n = 12) were used as reference. Histomorphometric analysis was performed for assessment of bone formation activity in HOs and reference bone. HOs were dissected with histological guidance into three zones: formed bone, zone of active bone formation, and zone with fibrous connective and fibrocartilagineous tissue. Relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 47 publications
0
19
1
1
Order By: Relevance
“…It should, however, be noted that overall bone content of TGF-b 2 was lower compared to the other TGF beta isoforms (see Table I). We also showed that the TGF-b 3 expression was increased (Toom et al 2007) while no difference on the protein level was seen in this study. It should be emphasized that in the tissues the protein level do not always correspond to the mRNA profile.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…It should, however, be noted that overall bone content of TGF-b 2 was lower compared to the other TGF beta isoforms (see Table I). We also showed that the TGF-b 3 expression was increased (Toom et al 2007) while no difference on the protein level was seen in this study. It should be emphasized that in the tissues the protein level do not always correspond to the mRNA profile.…”
Section: Discussioncontrasting
confidence: 62%
“…This was confirmed by the current study, since relatively little cartilage formation was found. We have earlier also shown the increased expression on TGF-b 2 and TGF-b 3 in the immature HOs as compared to the mature HOs, with the method, where beta-actin was used as a control for expression (Toom et al 2007). This study shows that the HO content of TGF-b 2 is clearly higher in the immature HOs, compared to the mature HOs and the increased expression thus leads to increased formation of TGF-b 2 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Recently, ectopic and heterotopic ossifications have been reported to be in association with high levels of expression of BMP2 (22). Here, we examined whether ANA regulates BMP activities with respect to ectopic bone formation.…”
mentioning
confidence: 98%